THE IMPORTANCE OF PHYSICAL EDUCATION IN THE FORMATION OF A STUDENT’S PERSONALITY - Khatamov Zafarjon Nazirjonovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article analyzes the importance of physical education classes for students of higher education institutions. Issues of influence of sports and physical culture on health, physical development and formation of student’s personality are considered.